Analysis of Management Strategies and Religious Beliefs of Families with Five or More Children - Arini Rizqina; Iradewi Cahyati; Rizky Asrul Ramadhan; Heni Ani Nuraeni (Journal Informatic, Education and Management (JIEM), 2026)
Indonesia in the contemporary demographic landscape is increasingly dominated by the norm of small nuclear families, while large families with more than five children are often seen as marginalized and burdened with social stigma. The narrative of state policies through Family Planning programs and modern economic discourse places the extended family as an "illegal" entity, associated with economic burdens, domestic turmoil, and parental attention deficits. This article dismantles these assumptions through a qualitative case study of a family of five children in a semi-urban environment. This study delves into the often over looked micro-sociological dynamics in macrostatistics, using in-depth interviews and participatory observations. The thematic analysis identified three main pillars of extended family resilience: (1) a stratified yet adaptive domestic management system, with a gender- and age-based division of labor for efficiency; (2) internalization of the value of responsibility through disciplinary repetition and collective supervision; and (3) the construction of religious beliefs "many children have plenty of sustenance" which functions as psychological capital and transcendent coping strategies in the face of economic uncertainty and social pressure. These findings challenge deficit narratives about the extended family and show how Islamic spirituality and traditional management combine to create solid subjective well-being.